ANALISIS OBJEK WISATA KEBUN TEH PTP NUSANTARA VI DANAU KEMBAR KECAMATAN GUNUNG TALANG KABUPATEN SOLOK - Apriyana, Fitriya; Bakaruddin, Bakaruddin; Erita, Yeni (Pendidikan Geografi, 2013)
Tourism sector is one of the characteristic multidimensi sector, that is not only refers to the internal factor, but eksternal too. Tourism sector demand compleks something supperfing facility can fulfill variast tourist that is, not only tourism domestic, but also tourism from foreign countries. This research to fine out information on how to power, how weaknesses, how the odds, how threats and how the strategies that made the Tea Gardens Attraction PTP Nusantara VI Danau Kembar Gunung Talang District of Solok regency.This research is a descriptive qualitative research . Analysis methods such as analysis of the system by using SWOT analysis. SWOT analysis is a systematic identification of factors that are expected to formulate a strategy to solve a problem. This analysis is based on the logic that maximizes the strengths and opportunities, but at the same time can minimize the weaknesses and threats.Research results showed: (1) The power possessed a beautiful natural landscape. Tourism activities that can be done at this location, among others, enjoying the scenery, tea walk, eco-tourism, agro-tourism, (2) weaknesses had not been exploited is the optimal tourism resources, which have not been provided adequate accessibility, accommodation is still lacking, and the lack of existing infrastructure, (3) Opportunity is owned by the attention and support of the national government towards tourism (4) Threats owned was a lack of understanding of the community and tourism (5) Strategies for Tea Gardens attraction PTP Nusantara VI Twin Lakes is developing a resource both tourist natural attractions and cultural tourism, provide and improve the quality of accessibility to the area attractions, providing special places to accommodate all the needs of travelers improve the quality of public education in order to be a good host and smart